The regulatory effect of TiO2 nanotubes loaded with graphene oxide on macrophage polarization in an inflammatory environment - Xu Cao; Bin Luo; Yanting Mu; Caiyun Wang; Ran Lu; Yao Yao; Su Chen (BMC, 2024)
Abstract Background Excessive inflammation is a major cause of implant failure. The surface morphology, hydrophilicity, and loading of biomaterials are major properties modulating anti-inflammatory macrophage activation. This paper investigates the regulatory effects of modifying the surface of Titanium dioxide nanotubes (TNTs) with graphene oxide (GO) on the polarization of mouse monocyte macrophages (RAW264.7). Methods TNT was produced by the anodic oxidation of titanium. GO was subsequently electrodeposited on the TNT to obtain a TNT-GO composite. The samples were characterised through scanning electron microscopy (SEM), Raman spectroscopy, and X-ray diffraction. RAW264.7 cells were separately seeded onto the surface of three groups of samples: pure Ti, TNT, and TNT-GO. Under the condition of lipopolysaccharide stimulation, the influence of the sample surfaces on the gene expression profiles was investigated through RNA sequence analysis. In addition, cell spreading was observed through SEM, cell adhesion and proliferation were analysed using the CCK8 assay, and the expression of inflammation-related factors was investigated by ELISA and cellular immunofluorescence staining. The production of reactive oxygen species (ROS) in the RAW264.7 cells on the surface of the three groups was detected via immunofluorescence staining. Results The CCK8 results indicated that the adhesion and proliferation of the RAW264.7 cells were reduced on the TNT and TNT-GO surfaces. ELISA results revealed significant differences in the pro-inflammatory factors tumour necrosis factor-α and interleukin-6 secretion among the three groups at 24 h (p < 0.05). The secretion of pro-inflammatory factors significantly reduced and the expression of anti-inflammatory factor IL-10 increased on the TNT and TNT-GO surfaces. The RNA sequencing, ELISA, and cell immunofluorescence staining test results suggested that the inflammatory response of M1 polarization was reduced and the M2 polarization of macrophages was induced on the TNT-GO surface, which may be attributed to the reduction in ROS production. Conclusions Under lipopolysaccharide stimulation, the inflammatory response of the RAW264.7 cells was reduced and the M2 polarization of macrophages was promoted on the TNT-GO surface, which may be caused by the reduced ROS production. Consequently, the designed TNT-GO material is promising for implants owing to its excellent inflammation regulation ability.